Avtentična besedila pri pouku francoščine kot tujega jezika - Lah, Meta (Vestnik za tuje jezike, 2010)
The present paper is aimed at providing a reflection on the use of authentic texts in French as a foreign language classroom. The author bases herself on an analysis of texts taken from four textbook sets (Le nouveau sans frontieres, Panorama, Campus and Rond point), which were or are still used in teaching French as a foreign language. Initially, a definition of authenticity and a survey of authentic material usage through history are provided. In the overview of the texts forming the corpus the texts are divided into authentic, adapted, apparently authentic and those for which no assumption can be made as to their authenticity. The authenticity analysis is also carried out by taking into account the analysis of categorisation into text types (according to Adam). The author proceeds from two premises, i.e. firstly she foresees that authentic texts will be present in all textbooks analysed and secondly, considering the greater accessibility of materials, that their presence will be more pronounced in recent textbooks. However, none of the two hypotheses is confirmed, as authentic texts are found in the first three textbook sets, but not in the most recent one, while their presence is most pronounced in the oldest textbook set, i.e. in Le nouveau sans frontieres. The result of the analysis is thus somehow surprising given the overall accessibility of all kinds of authentic materials. In the author's opinion more authentic texts should be included into textbooks to thus enhance the purposefulness of the foreign language classroom.
Keywords: francoščina; French; tuji jeziki; učbeniki; avtentična besedila; tipi besedil; didactic method; didaktika; metodika